The Effect of Profitability and Environmental Performance on Firm Value of Islamic Commercial Banks in Indonesia - Farah Ivana; Syarifah Mauli Masyithah; Indrakesuma; Muhammad Ridha Ramli; Syafira Yunidar; Ferroz Firdaus (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the influence of profitability and environmental performance on the value of companies in Sharia Commercial Banks in Indonesia for the 2020–2023 period. Profitability is measured using Return on Assets (ROA), while environmental performance is measured by PROPER. The value of the company is proxied by the Price to Book Value (PBV). The research method used is a quantitative approach with multiple linear regression analysis. The results of the study show that profitability has a positive and significant effect on the company's value partially. Environmental performance does not have a significant effect partially, but simultaneously, profitability and environmental performance have a significant effect on the company's value. These findings confirm the importance of strengthening profitability and implementing sustainable environmental management to increase company value. This research is expected to be a reference for practitioners and academics in the development of sustainability-oriented Islamic financial management.